The role of consequences of moral action in maximizing moral elevation. Issue 4 (2nd October 2018) - Yao, Zhuojun; Enright, Robert
Abstract: Moral elevation is described as a state of positive emotion that includes uplifting feelings, positive views of humanity and a desire to be a better person. Numerous empirical studies have demonstrated that elevation has powerful effects on people's moral intention and behavior. The next step is to investigate how to maximize the emotion of elevation. According to the evolution of moral elevation research and the theory of moral disgust, we hypothesized that the consequences of moral action would influence moral elevation. The results of two studies in the present research (Study 1: N = 122, average age = 36.96 years; Study 2: N = 232, average age = 23.93 years) demonstrated that moral acts with good consequences were more effective in inducing moral elevation than moral acts with bad consequences. The implications for research and practice are discussed.